Life Cycle Assessment of Olive Oil Tin and Plastic Containers - Yahya Saleh (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
For a long period of time, Palestine has witnessed significantly noticeable shortages and scarcities of natural resources, namely, water and energy resources. Many industries adversely contribute in the continuous consumption and depletion of such natural resources. Among these, there are the packaging materials industries producing plastic and metal packaging containers for holding liquid products. Examples of such containers are tin and plastic containers used for packaging and storing olive oil in Palestine. These primary two packaging systems differ in their environmental impacts during the stages of processing, manufacturing, distribution, transportation, usage and disposal. More specifically, they differ in consumption of natural resources such as water, energy, and land use (solid wastes generation), as well as in their contribution to human toxicity and health problems (dust) and resulted industrial noise. This work aims at evaluating and comparing the potential environmental impacts of tin and plastic containers of olive oil via employing life cycle assessment (LCA) based on International Standardization Organization (ISO) standards (namely, ISO 14040, ISO 14041, ISO14042, and ISO 14043). The life cycle inventory and impact assessments considered the above-mentioned significant environmental domains (water, energy, solid waste, dust and industrial noise) in conducting the LCA. Within the boundaries of both systems, the LCA analysis showed that tin containers (16 Ls) outperformed plastic containers (16 L) in terms of having less environmental impacts.